University of Oxford: Open Research Position Statement, June 2024 - Dally, K; Callaghan, S; Casci, T; Sansone, S-A (University of Oxford, 2024)
The University of Oxford encourages a culture of openness, transparency, and collaboration in research. We believe that applying principles of openness and accessibility to research processes and research outputs has strong benefits for research quality and impact, by improving reuse and reproducibility, and underpinning research integrity. This Statement provides a framework for University researchers to conduct and disseminate research in a manner that promotes the sharing and accessibility of knowledge, trust in researchers and institutions, and societal impact. This Statement has been informed by and aligns to external policy frameworks and sector concordats and applies to all staff and students of the University who conduct research, regardless of funding source. Externally funded researchers are expected to act in accordance with the requirements of those funding their research and regulatory bodies. This Statement is archived in ORA (Oxford University Research Archive) at http://dx.doi.org/10.5287/ora-pdppwjwmn, and the text is free for others to use and adapt.